The Word of God as Key to Christian Worship - Katz, Peter (Scottish journal of theology, 1952)
In a service of the right kind God speaks to the congregation, and the Holy Spirit opens the hearts and lips of the congregation to reply. The means by which the inscrutable God comes out of the ‘Light unapproachable’ is His ‘Word’. It has been the will of God to limit His self-revelation to mediation through the ‘Word’. This self-revealing ‘Word’ makes itself known in two ways:Firstly, God became man in Christ. He has thus entered our field of vision. From Christ's words and acts and from His character discernible behind them, the Father's nature, heart and will towards us are discerned, so far as such discernment is given to man. Christ is that aspect of God which is turned towards us. He reflects the rays of God, so far as human eyes can bear their light. As making known God's heart and will, Christ is therefore in a special sense ‘God's Word’. To describe Christ as the Word of God is to give a fully adequate picture. It is as the Eternal Word of God that the Risen Lord is in the midst of His faithful.